George W. Goethals papers - Goethals, George W. (George Washington), 1858-1928.
Correspondence, memoranda, diaries, reports, clippings, scrapbooks, maps, blueprints, photographs, and other papers relating chiefly to construction of the Panama Canal and to Goethals's term as governor of the Canal Zone. Also documents his service as general manager of the United States Shipping Board Emergency Fleet Corporation, chairman of the board appointed to report on the Adamson Eight-Hour Law which established an eight-hour workday for interstate railroad workers, and fuel administrator of New York State dealing with coal shortages from the 1922 Anthracite Coal Strike, Pa. Correspondents include Newton Diehl Baker, John Barrett, Joseph Bucklin Bishop, William Herbert Bixby, Sol Bloom, Edward William Bok, William Edgar Borah, Josephus Daniels, Edwin Denby, Lindley M. Garrison, William Crawford Gorgas, A.W. Greely, Chester Harding, Harry F. Hodges, Robert Lansing, Henry Cabot Lodge, William Loeb, M.O. Lorenze, A.T. Mahan, John J. Pershing, Franklin D. Roosevelt, Theodore Roosevelt, Francis Bowes Sayre, William L. Sibert, Henry L. Stimson, William H. Taft, Joseph P. Tumulty, and Woodrow Wilson.
Microfilm edition of desk diaries, 1918-1919, available
Microfilm produced from originals in the Manuscript Division.
Governor of the Canal Zone, army officer, and engineer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Barrett, John, -- 1866-1938 -- Correspondence; Bishop, Joseph Bucklin, -- 1847-1928 -- Correspondence; Bixby, William Herbert, -- 1849-1928 -- Correspondence; Bloom, Sol, -- 1870-1949 -- Correspondence; Bok, Edward William, -- 1863-1930 -- Correspondence; Borah, William Edgar, -- 1865-1940 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Denby, Edwin, -- 1870-1929 -- Correspondence; Garrison, Lindley M. -- 1864-1932 -- Correspondence; Gorgas, William Crawford, -- 1854-1920 -- Correspondence; Greely, A. W. -- 1844-1935 -- Correspondence; Harding, Chester, -- 1866-1936 -- Correspondence; Hodges, Harry F. -- 1860- -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Loeb, William, -- 1866-1937 -- Correspondence; Lorenze, M. O. -- Correspondence; Mahan, A. T. -- 1840-1914 -- Correspondence; Pershing, John J. -- 1860-1948 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Sayre, Francis Bowes, -- 1885-1972 -- Correspondence; Sibert, William L. -- 1860-1935 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Tumulty, Joseph P. -- 1879-1954 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Canal Zone. -- Office of the Governor; United States Shipping Board Emergency Fleet Corporation; Anthracite Coal Strike, Pa., 1922.; Canals -- Panama; Eight-hour movement -- United States; Fuel trade -- United States; Labor laws and legislation -- United States; Merchant marine -- United States; Railroads -- Employees; Strikes and lockouts -- Pennsylvania; Canal Zone -- History; Panama Canal (Panama); Army officers; Engineers; Governors -- Canal Zone